Answer:
x = - 9, x = 10
Step-by-step explanation:
Given
x² - x - 90 = 0
Consider the factors of the constant term (- 90) which sum to give the coefficient of the x- term (- 1)
The factors are - 10 and + 9, since
- 10 × 9 = - 90 and - 10 + 9 = - 1 , thus
(x - 10)(x + 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 10 = 0 ⇒ x = 10
x + 9 = 0 ⇒ x = - 9
lesser x = - 9
greater x = 10
45 :)))))))))))))))))))))))))))))))
<span>A rule that represents this function is y = (x + 8)².</span>
The rule looks like √y = (x + 8)
Now square both sides
<span>y = (x + 8)²</span>
y = x² + 16x + 64
<span>I am hoping that this answer has satisfied your query and it will
be able to help you in your endeavor, and if you would like, feel free to ask
another question.</span>
Answer:
try x= 4z/y
Step-by-step explanation:
Answer:
the answer is $50 for the full price of the sweater
Step-by-step explanation:
if you know $20 is 40% what is 20% it is $10 and then multiple it by 5 because 20 times 5 is 100 and you get 50